Imagination and Art: Explorations in Contemporary Theory - Moser, Keith,; Sukla, Ananta Ch., (Value Inquiry Book Series ;, 2020)
This transdisciplinary project represents the most comprehensive study of imagination to date. The eclectic group of international scholars who comprise this volume propose bold and innovative theoretical frameworks for (re-) conceptualizing imagination in all of its divergent forms. Imagination and Art: Explorations in Contemporary Theory explores the complex nuances, paradoxes, and aporias related to the plethora of artistic mediums in which the human imagination manifests itself. As a fundamental attribute of our species, which other organisms also seem to possess with varying degrees of sophistication, imagination is the very fabric of what it means to be human into which everything is woven. This edited collection demonstrates that imagination is the resin that binds human civilization together for better or worse.